Effect of EGR routing on efficiency and emissions of a PPC engine. (April 2019) - Dimitrakopoulos, Nikolaos; Belgiorno, Giacomo; Tunér, Martin; Tunestål, Per; Di Blasio, Gabriele
Highlights: High load favors mixed route EGR, low load favors short route EGR. Effect both on NOx and soot production when moving from SR EGR to LR EGR. Speed/load based EGR route switching has positive effect on gas exchange efficiency. Abstract: In order to significantly improve engine efficiency and reduce exhaust emissions at the same time, new radical combustion concepts have emerged. Gasoline partially premixed combustion (PPC) is one of them, with early results showing high gross indicated efficiency. To achieve that, PPC relies on high EGR (exhaust gas recirculation) use, with numbers that can reach up to 50%. Such a high amount of EGR poses a great demand on the gas exchange system, especially if it is not optimized for these requirements. A recent advancement that can provide high EGR rates especially under PPC conditions is the use of low pressure EGR, where gases are removed after the turbine and mixed with the intake air before the compressor. Experiments with the use of PPC and two different EGR routes were performed on a light duty Euro 6 2 L diesel engine. EGR sweeps between 100% use of long route to 100% short route under different conditions were performed. Gross indicated mean effective pressure (IMEPg) was kept around 10 bar, while four different speeds were used, 1200, 1800, 2400 RPM, as well as a reoccurring New European Driving Cycle (NEDC) speed-load point at 1500 RPM. To keep the fuel effects on combustion at a minimum, PRF 75 (Primary Reference Fuel) was used throughout the experiments. Results show that by combining EGR from both routes, generally, an optimum gas exchange efficiency can be found by splitting the EGR through both routes. This can be attributed to higher turbocharger efficiency due to better flow over the compressor regardless of engine load and speed. Emission wise, NOx emissions get an increase as EGR is moved from long route to short route, while soot emissions see an opposite trend for the same conditions. Based on these first results, a mixed EGR, or a long route system can be more beneficial for PPC type of engine applications.